D-L DOUBLETS IN CLASSICAL ARABIC AS EVIDENCE OF THE PROCESS OF DE-LATERALISATION OF DĀD AND DEVELOPMENT OF ITS STANDARD REFLEX - Corriente, F. (Journal of Semitic studies, 1978)
F. CORRIENTE; D-L DOUBLETS IN CLASSICAL ARABIC AS EVIDENCE OF THE PROCESS OF DE-LATERALISATION OF DĀD AND DEVELOPMENT OF ITS STANDARD REFLEX, Journal of Semitic